2011
DOI: 10.1007/s11745-011-3546-0
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Glucosylceramide Enhances Cornified Envelope Formation via Transglutaminase Expression and Involucrin Production

Abstract: In this study, we investigated whether dietary glucosylceramide (GlcCer) and its metabolite sphingoid bases, sphingosine (SS), phytosphingosine (PS), sphingadienine (SD) and 4-hydroxysphingenine (4HS), influence cornified envelope (CE) formation. CE is formed during terminal differentiation of the epidermis through crosslinking of specific precursor proteins by transglutaminases (TGases), and is essential for the skin's barrier function. Oral administration of GlcCer (0.25 mg/day) for 14 consecutive days drama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 36 publications
1
33
0
Order By: Relevance
“…Although a single dose of UVB irradiation perturbs the skin barrier in hairless mice and causes an increase in TEWL at 4 d after irradiation, oral administration of GlcCer dramatically reduced TEWL at 4 d after irradiation in our previous study. 16) In the present study, we observed that the localization and expression of claudin-1 in the epidermis were improved by dietary GlcCer at 4 d after irradiation, and this coincided with the GlcCer-induced improvement in TEWL. It has also been reported that claudin-1 is important for the later recovery of TJ barrier function following UVB radiation in mice.…”
Section: )supporting
confidence: 76%
See 1 more Smart Citation
“…Although a single dose of UVB irradiation perturbs the skin barrier in hairless mice and causes an increase in TEWL at 4 d after irradiation, oral administration of GlcCer dramatically reduced TEWL at 4 d after irradiation in our previous study. 16) In the present study, we observed that the localization and expression of claudin-1 in the epidermis were improved by dietary GlcCer at 4 d after irradiation, and this coincided with the GlcCer-induced improvement in TEWL. It has also been reported that claudin-1 is important for the later recovery of TJ barrier function following UVB radiation in mice.…”
Section: )supporting
confidence: 76%
“…Moreover, in the skin of SDStreated mice, dietary GlcCer induced increased expression of CE formation-related genes and TJ-related genes at 2 d after SDS treatment. 15) It has been suggested that dietary GlcCer improves CE formation by inducing the production of CE-related molecules, 16) but the influence of dietary GlcCer on TJs has not been studied.…”
Section: )mentioning
confidence: 99%
“…These findings indicate that dietary GC can play an important role in maintaining a healthy skin barrier condition and in promoting recovery from an impaired skin barrier by enhancing CE and TJ formation at the gene expression level. We have recently shown the increased expression of Tgm-1 mRNA 35) and claudin-1 and involcrin proteins in GC-fed barrierperturbed mice skin after UV exposure (data are not shown). These results also suggest the relationship between CE-and TJ-related genes in the dietary GC effect against skin barrier perturbation.…”
Section: Discussionmentioning
confidence: 91%
“…Indeed, we have observed a significant increase of TGase-1 in the skin of GC-fed mice following barrier perturbation by UV exposure. 35) TGase-1 is known to catalyze the formation of ester bonds between specific glutaminyl residues of involucrin which is localized at the outmost face of the CE and corneocyte lipid envelope and thus contributes to mature lamellar membrane formation in SC and to skin barrier homeostasis. [36][37][38] An increase of TGase-1 might therefore contribute to barrier recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary plant sphingolipids with sphingoid bases distinct from those found in mammals are able to prevent the formation of aberrant crypt foci in 1,2-dimethylhydrazine-treated mice (7,8). In addition, the beneficial effects of dietary plant sphingolipids have been reported in patients with atopic eczema and in model mice of skin damage, although the compositions of sphingoid bases in the stratum corneum of mammals are quite different from those of dietary glucosylceramide derived from plant sources (9)(10)(11). Our previous findings suggest that the skin barrier-improving effect of dietary sphingolipids might be due to the activation of ceramide synthesis in the skin, rather than to the direct reutilization of dietary sphingolipids (12).…”
mentioning
confidence: 99%